Paratesticular Embryonal Rhabdomyosarcoma with Lung Metastasis – A Rare Case Report - Ganapathi, Anusha; J, Thanka; D'Cruze, Lawrence; G, Barathi; K, Natarajan; Scott, Julius Xavier (Annals of Pathology and Laboratory Medicine, 2020)
Paratesticular rhabdomyosarcomas (RMS) are very rare malignant tumors arising from the mesenchymal tissues of tunica, epididymis or spermatic cord. They present as painless hard masses in inguinoscrotal region, and large tumors can be mistaken for testicular tumors. They can spread to retroperitoneal lymph nodes or hematogenously metastasize to lung, bones and bone marrow. Here, we report a case of Embryonal RMS with spindle cell component presenting with painless scrotal mass and lung metastasis at initial diagnosis.